Enhanced Efficacy of Thiosemicarbazone Derivative-Encapsulated Fibrin Liposomes against Candidiasis in Murine Model - Azmat Ali Khan; Amer M. Alanazi; Nawaf Alsaif; Nasser Algrain; Tanveer Ahmad Wani; Mashooq Ahmad Bhat (MDPI AG, 2021)
Candida albicans is the most studied species for the candidiasis infection and is becoming resistant towards existing antifungal drugs. Considering this, in the current study, we developed and characterized a fibrin liposome-based formulation encapsulating a novel thiosemicarbazone derivative, 2C, and evaluated its antifungal efficacy against murine candidiasis. The 2C-containing formulation was prepared by encapsulating 2C within the liposomes (2C-L) that were further encapsulated in the fibrin beads (2C-FL). The in-house synthesized 2C-FLs were spherical with a zeta potential of −34.12 ± 0.3 mV, an entrapment efficiency of 72.6 ± 4.7%, and a loading efficiency of 9.21 ± 2.3%, and they showed a slow and sustained release of 2C. Compared to free 2C, the formulation was non-toxic and exhibited serum stability, increased tissue specificity, and penetration. The 2C-FL formulation had a minimum inhibitory concentration (MIC) value of 4.92 ± 0.76 µg/mL and was able to induce apoptosis and necrosis in C. albicans in vitro. The administration of 2C-FL in C. albicans-infected mice prolonged their survival and antifungal effects when compared with the free 2C. The 2C-FL antifungal therapy significantly reduced the fungal burden and displayed an improved survival rate. In conclusion, the 2C thiosemicarbazone derivative possesses a potent antifungal activity that became more advantageous upon its encapsulation in the fibrin liposome delivery system.